HUBUNGAN TINGKAT KEGAWATDARURATAN (TRIASE) DENGAN TINGKAT KECEMASAN KELUARGA PASIEN DI INSTALASI GAWAT DARURAT RSUD dr.ISKAK TULUNGAGUNG: CORRELATIONAL OF EMERGENCY LEVELS (TRIASE) WITH PATIENT'S FAMILY ANXIETY LEVEL IN THE EMERGENCY DEPARTMENT IN RSUD dr.ISKAK TULUNGAGUNG - Manggar Purwacaraka; Shulhan Arief Hidayat; Farida (Stikes Pamenang, 2022)
Abstrak : Kecemasan merupakan respon emosional terhadap penilaian yang menggambarkan keadaan khawatir, gelisah, takut, tidak tentram disertai berbagai keluhan fisik. Selama proses perawatan, kecemasan tidak hanya dirasakan oleh seorang pasien, namun dapat juga dialami oleh keluarga pasien. Keluarga pasien merupakan salah satu pemegang penuh keputusan, ketika pasien dalam keadaan darurat maupun kritis dan harus diberikan penanganan segera. Tujuan penelitian untuk mengetahui Hubungan Tingkat Kegawatdaruratan (Triase) dengan Tingkat Kecemasan Keluarga Pasien. Desain penelitian yang digunakan yaitu analitik cross-sectional, penelitian dilaksanakan di Instalasi Gawat Darurat RSUD dr. Iskak Tulungagung. Sampel penelitian ini adalah keluarga pasien dengan teknik consecutive sampling, didapatkan sampel 30 responden. Data yang dikumpulkan dengan menggunakan kuesioner HARS. Data diolah dengan cara editing, coding, scoring, tabulating dan analisis dengan uji statistik Spearman’s rho. Hasil penelitian uji statistik Spearman’s rho, didapatkan nilai p = 0,000 untuk uji hubungan tingkat kegawatdaruratan (triase) dengan tingkat kecemasan keluarga pasien. Kesimpulan dari penelitian ini bahwa semakin tinggi tingkat kegawatdaruratan (triase) pasien maka akan mempengaruhi kecemasan keluarga pasien. Rekomendasi bagi rumaah sakit khususnya di Instalasi Gawat Darurat diharapkan lebih meningkatkan komunikasi antara tenaga kesehatan dengan keluarga pasien. Untuk mereduksi kemungkinan kecemasan oleh keluarga. kata kunci : tingkat kegawatdaruratan (triase), tingkat kecemasan Abstract : Anxiety is an emotional response to an assessment that describes a state of worry, anxiety, fear, restlessness accompanied by various physical complaints. During the treatment process, anxiety is not only felt by a patient, but can also be experienced by the patient's family. The patient's family is one of the full decision makers, when the patient is in an emergency or critical condition and must be given immediate treatment. The purpose of the study was to determine the Correlation of Emergency Levels (Triase) with Patient's Family Anxiety Level in the Emergency Department in RSUD dr. Iskak Tulungagung. This Study design was association analytic with a cross-sectional approach, the research was carried out in the Emergency Installation of RSUD dr. Iskak Tulungagung. The sample of this study was the patient's family with consecutive sampling technique, obtained a sample of 30 respondents. Data were collected using the HARS questionnaire. The data were analyzed by Spearman's rho statistical test. The results showed that 12 respondents (40%) entered the yellow triage and 9 respondents (30%) had moderate levels of anxiety. The results of the bivariate test obtained p value = 0.000 which means that there is a relationship between the level of emergency (triage) and the level of anxiety of the patient's family with a correlation coefficient of -0.748 which means that the higher the respondent's emergency, the higher the respondent's anxiety level. This negative result occurs because the coding for the first emergency level is Red Triage, while the code for the first level of anxiety is not anxious. There is a significant relationship, this can be caused because when there are respondents who enter the red triage, the family's assumption is that the patient's hope for recovery is getting smaller so that family anxiety increases. The conclusion of this study is that the higher the level of emergency (triage) of the patient, the higher the level of anxiety of the patient's family. Recommendations for hospitals, especially in the Emergency Room, are expected to further improve communication between health workers and patients' families. To reduce the possibility of anxiety by the family. Keywords : Level Of Emergency (Triage), Anxiety Level